Direct oxygen imaging in titania nanocrystals - Lu, Weigang; Bruner, Britain; Casillas, Gilberto; Mejía Rosales, Sergio; Farmer, Patrick J.; Yacamán, Miguel José (IOP Publishing, 2012)
Recently, rutile nanotwins were synthesized using high temperature organic solvent methods, yielding two kinds of common high-quality rutile twinned nanocrystals, (101) and (301) twins, accompanied by minor rutile nanorods (Lu et al 2012 CrystEngComm 14 3120–4). In this report, the atomic structures of the rutile and anatase nanocrystals are directly resolved with no need for calculation or image simulation using atomic resolution STEM techniques. The locations of the oxygen rows in the rutile twins’ boundaries are directly determined from both HAADF images and ABF images. To the best of our knowledge, this is the first time oxygen columns have been distinguished in rutile twin boundaries using HAADF and BF imaging.